STRATEGI KEPEMIMPINAN KEPALA DESA DALAM MEWUJUDKAN TRANSPARANSI DAN AKUNTABILITAS PENGELOLAAN DANA DESA DI DESA JUHAR BARU, KECAMATAN GALANG, KABUPATEN DELI SERDANG - Sarah Lestari Tampubolon; Friska Lorentina Purba; Putri Amelia Simbolon; Unedo Sean Hillinois Sinaga; Drs. Halking, M.Si (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
In the discussion of Mini Research Group 3, a phenomenon regarding long-term village fund management was raised, regarding transparency and accountability by village government leadership and community oversight, specifically in Juhar Baru Village, Galang District, Deli Serdang Regency. In this case, of course, there is a question that we will raise and we will include in the Mini Research report regarding budget efficiency or fund management for Juhar Baru Village. Is the allocation of funds used by the Juhar Baru Village government on target or not? For example, Direct Cash Assistance (BLT), electricity, water, educational facilities or hospitals and so on. One of our group members, Friska Lorentina Purba, acted as a facilitator to make it easier to ask several questions regarding the problem of village fund management in Juhar Baru Village. This research employs qualitative research methods, involving direct fieldwork to observe current problems or phenomena, and relying on several sources from journals, articles, and books to further strengthen the author's arguments. The results of this study indicate that the management of village funds, allocation of funds, and village budget expenditures are highly transparent and accountable, in line with the strategy implemented by the Juhar Baru village head. This is because the village head and village officials have a strong collaboration in developing village infrastructure, as evidenced by the infrastructure development process outlined in the research findings. However, despite the need for improvements in education, which is still lacking, progress in Juhar Baru Village is already evident when weighed against other needs.